2021
DOI: 10.3390/su131910849
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Intellectual Capital into the Green Board Committee to Enhance Firm Performance

Abstract: The purpose of this study was to conceptualise a framework that reflects an intertwined relationship between the green board committee and firm performance. Agency and stakeholder theories hold a basic notion of supporting the relationship between the green board committee and firm performance. The moderating role of intellectual capital (IC) was introduced in the intertwined relationship between green board committees and firm performance based on a resource-based view theory. This study proposes a new measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 77 publications
0
22
0
4
Order By: Relevance
“…Furthermore, the board of directors must devote significant attention to developing green governance that enables green innovation methods (Shah et al , 2021. However, the authors would like to draw attention to women's participation at managerial and board levels which was found to be lower than that in Malaysian (Lim et al 2019;Guizani and Abdalkrim 2022) and Indonesian (Nainggolan et al 2022) corporate governance code.…”
Section: Practical Implicationmentioning
confidence: 96%
“…Furthermore, the board of directors must devote significant attention to developing green governance that enables green innovation methods (Shah et al , 2021. However, the authors would like to draw attention to women's participation at managerial and board levels which was found to be lower than that in Malaysian (Lim et al 2019;Guizani and Abdalkrim 2022) and Indonesian (Nainggolan et al 2022) corporate governance code.…”
Section: Practical Implicationmentioning
confidence: 96%
“…al., 2022;Shah et al, 2021). However, the author would like to draw attention to women's participation at managerial and board levels was found to be lower than in Malaysian(Guizani & Abdalkrim, 2022;Lim et al, 2019) and Indonesian(Nainggolan et al, 2022) corporate governance code.Thereby boosting the business's triple bottom line and allowing the rm to relate to the market and investors(Lai et al, 2021).…”
mentioning
confidence: 88%
“…The global economy is currently facing a significant crisis due to the COVID- 19 Recent research has shown that organizations with a strong commitment to green intellectual capital have been able to weather the economic downturn caused by the pandemic better than those without such commitment (Rodrigues et al, 2017). This is because green intellectual capital can lead to cost savings, such as through energy efficiency, and can also increase revenue through the development of new green products and services (Shah et al, 2021). Additionally, organizations with green intellectual capital are more likely to have a positive reputation, which can attract customers and investors (Li et al, 2020).…”
Section: Green Intellectual Capital In Crisis Momentsmentioning
confidence: 99%
“…However, while green intellectual capital can provide a competitive advantage in times of economic crisis, it can also be a significant investment. Organizations must invest in the development and training of their workforce in order to build green intellectual capital (Shah et al, 2021). Furthermore, organizations must also implement environmentally sustainable business practices, which can also be costly (Li et al, 2020).…”
Section: Green Intellectual Capital In Crisis Momentsmentioning
confidence: 99%
See 1 more Smart Citation